Impact of Temporal Variation of Chlorophyll‐Specific Absorption on Phytoplankton Phenology Observed From Ocean Color Satellite: A Numerical Experiment. Issue 12 (27th November 2020) - Lee, Zhongping; Shang, Shaoling; Zhang, Shuai; Wu, Jinghui; Wei, Guomei; Wu, Xiuling
Abstract: We designed a numerical experiment to characterize the impact of a dynamic chlorophyll‐specific absorption coefficient ( a ph ∗ ) on the retrieved temporal pattern of chlorophyll concentration ( Chl ) from ocean color ( R rs ). It is found that, even for oceanic waters, without consideration of the temporal variation of a ph ∗, Chl derived from a synthesized annual R rs using the "standard" ocean color algorithms will generate false dynamic patterns of Chl or questionable phytoplankton phenology. For instance, for an annual Chl with spring and fall blooms, the inverted Chl from R rs could show a delay of spring bloom by ∼1–3 weeks, along with a perceived earlier appearance of fall bloom or a false bloom during summer. These results highlight the complex relationships between R rs (an optical property) and Chl (a biological property) in aquatic environments, in particular, the importance and necessity to characterize and understand the temporal variations of a ph ∗ . Plain Language Summary: The chlorophyll‐specific absorption coefficient ( a ph ∗ ) serves as a link between phytoplankton absorption coefficient and chlorophyll concentration ( Chl ). Because ocean color ( R rs ) is driven by absorption and backscattering coefficients, a change of either a ph ∗ or Chl can modify R rs . Consequently, even for "Case‐1" waters, a change of R rs may not necessarily represent a change of Chl, unless a ph ∗ co‐varies with Chl . Measurements at the Hawaii Ocean Time‐series showed that a ph ∗ can be ∼40% higher in summer than in winter, which is ∼3 times of that predicted from the range of Chl . Such a behavior suggests there could be considerable uncertainties in the temporal pattern of Chl derived from ocean color, where such temporal variations are the base to study phytoplankton phenology. We thus used synthesized annual time series of Chl and a ph ∗ to evaluate the impact of a dynamic a ph ∗ on the temporal variation of Chl retrieved from R rs and found that there could be a large difference in the timing of maximum Chl as well as the duration of blooming. The results emphasize the importance to characterize and understand the dynamics of a ph ∗ in order to obtain accurate temporal patterns of Chl from satellite ocean color measurements, which is crucial for phytoplankton phenology study. Key Points: The omission of the temporal variation of a ph ∗ in ocean color inversion could result in false chlorophyll temporal pattern or phytoplankton phenology It is important and necessary to characterize the spatial and temporal variation of a ph ∗ for better retrieval of chlorophyll dynamics a ph (440) is a more reliable output than Chl from ocean color remote sensing at least for oceanic waters